Information System Strategic Planning at Institut Agama Islam Negeri Ternate - Sudarman Sudarman; Asmarani Pratama Y. Hadad; Abd. Haris Abbas (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2023)
Institut Agama Islam Ternate (IAIN) is one of the universities that run business processes in terms of educational services. IAIN Ternate has implemented information systems and information technology (IS/IT) to support its business processes. However, the implementation of IS/IT has not been equipped with strategic planning, so all forms of procurement, development, and maintenance of IS/IT are only available upon request and are not yet aligned with the organization's strategic plan. This research was conducted to design organizational needs into an IS/IT strategic plan at IAIN Ternate using the Ward and Peppard Framework. This research was conducted using interviews and focus group discussions (FGD) with the leaders and staff of the units at IAIN Ternate. The tools used for the analysis of the organization's internal environment are SWOT and value chain; for the analysis of the organization's external environment, PESTLE and McFarlan Grid are used to map the application portfolio. Based on the results of the study, IAIN Ternate has utilized IS and IT. To achieve the vision, mission, and objectives of IAIN Ternate, it is recommended that IS/IT become a priority for development. The IT Strategic Plan consists of an IS strategy, an IT strategy, and an IS/IT management strategy.